Managers’ perceptions of human capital: Important attributes in the Malaysian market - Daud, Salina (2010)
A knowledge based economy can be achieved through the development of human capital. Higher Education Institutions, as the main providers of human capital, play a crucial role in producing graduates that meet industry needs.This study investigates the potential gap between important dimensions of graduates’ attributes of a Higher Education Institution and the actual performance of these graduates during their employment. The attributes and the performance of these graduates are considered in four broad areas, namely knowledge, skills, abilities and personality.The results of this study will assist the Higher Education Institution in identifying the most important dimensions in the curriculum taught to the students in relation to knowledge, skills, abilities and personality, relevant to the Malaysian market.